Exploration of head gesture control for hearing instruments. (23rd September 2014) - Tessendorf, Bernd; Gravenhorst, Franz; Roggen, Daniel; Stiefmeier, Thomas; Strohrmann, Christina; Tröster, Gerhard; Derleth, Peter; Feilner, Manuela
In this work, we investigated the BENEFIT of head gestures as a user interface to control hearing instruments (HIs). We developed a prototype of a head–gesture–controlled HI, which was based on a customised wireless acceleration sensor for unconstrained and continuous real–time monitoring of the user's head movements. We evaluated the system from a technical point of view and achieved a precision of 96% and a recall of 97% for spotting the two head gestures used: tilting the head to the left and right side. We further evaluated the system from the user's point of view based on the feedback from 6 hearing–impaired HI users (4 men, 2 women, age 27-60).We compared our head–gesture–based control to existing HI user interfaces: HI–integrated buttons and HI remote control. We found that the benefit of the different HI interaction solutions depends on the user's current situations and that all participating HI users would appreciate head gesture control as an additional, complementing user interface.